Adult glomerular diseases in east zone and zonal prevalence in India: an Omnium Gatherum - Dogra, Pavitra M.; Shanmugraj, G.; Jana, Sebabrata; Hooda, Ashok K.; Sharma, Alok (International Journal Of Community Medicine And Public Health, 2019)
Background: India is a vast country with four geographical zones. Zonal heterogeneity amongst prevalent adult glomerular diseases is expected and has not been analysed in past studies. Methods: We conducted clinico-histological correlation of 290 kidney biopsies for adult glomerular diseases (GD) at tertiary teaching hospital in Eastern India between January 2013 and December 2015 and compared our data with biopsy data from other geographical zones in India to evaluate zonal variability (intra/inter) of adult glomerular diseases. Results: Males dominated all clinical syndromes except subnephrotic proteinuria (SbNP). IgA Nephropathy (IgAN, 41.1%) and Focal Segmental glomerulosclerosis (FSGS, 17.3%) were prevalent primary GD whereas Lupus nephritis (LN, 52.2%) and diabetic nephropathy (DN, 23.9%) were prevalent secondary GD. IgAN (44.4%) and LN (33.2%) dominated SbNP group whereas FSGS (30.2%) and Membranous nephropathy (MGN, 22.3%) dominated nephrotics. Mean eGFR (CKD-EPI) amongst EyRD and RPRF was 39.6±12.9 and 6.2±2.9 ml/min/1.73m2 respectively. In contrast, biopsies from East India showed MCD prevalence, followed by FSGS. Kidney biopsy data from West India showed MCD prevalence whereas Northern India and South India studies showed FSGS and MCD prevalence, but later data showed an IgAN emergence, as in our data. Conclusions: There is considerable heterogeneity in prevalent adult glomerular diseases in different geographical zones (inter and intra) in India. FSGS and MCD were the most prevalent in all zones. Our study showed IgAN prevalence in East Zone, similar to South India. Reason was, increased number of kidney biopsies in EyRD (eGFR 30-60 ml/min) and subnephrotic proteinuria.